Digital Efficiency of the Khanza Application for Nursing Care Documentation at Prof. Dr. Aloei Saboe Hospital - Ardiyansyah Dumako; Hartati Inaku; Sabirin B. Syukur (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Background: Nursing care documentation is an important part of health care that must be carried out completely, accurately, and on time. The implementation of digital documentation through the Khanza Hospital Management Information System (SIMRS) application is expected to be able to improve the work efficiency of nurses and support the completeness of nursing care documentation. However, the difference in perception of the efficiency of using the Khanza application by nurses has the potential to affect the completeness of the documentation produced. Objective: To determine the influence of the digital efficiency of the Khanza application on the completeness of nursing care documentation at Prof. Dr. Aloei Saboe Hospital, Gorontalo City. Methods: This study used an analytical descriptive design with a cross sectional approach. The research sample amounted to 37 nurses who were selected using purposive sampling techniques in Building III of Prof. Dr. Aloei Saboe Hospital. Data was collected using the Khanza application efficiency questionnaire and a nursing care documentation observation sheet. Data analysis was carried out using the Chi-Square test. Results: The results showed that the majority of nurses rated the efficiency of the Khanza application to be in the efficient category. All nurses with a perception of efficiency and are quite efficient have efficient nursing care documentation, while in the category of sufficiently efficient there is still inefficient documentation. The Chi-Square test showed a value of p = 0.000 (p < 0.05). Conclusion: The efficiency of the Khanza application has a significant effect on the completeness of nursing care documentation. Optimizing the use of the Khanza application through continuous training and supervision is needed to improve the quality of nursing documentation in hospitals.